Tetraspanin CD37 contributes to the initiation of cellular immunity by promoting dendritic cell migration. Issue 5 (25th March 2013) - Gartlan, Kate H.; Wee, Janet L.; Demaria, Maria C.; Nastovska, Roza; Chang, Tsz Man; Jones, Eleanor L.; Apostolopoulos, Vasso; Pietersz, Geoffrey A.; Hickey, Michael J.; van Spriel, Annemiek B.; Wright, Mark D.
<x xml:space="preserve">Abstract</x> Previous studies on the role of the tetraspanin CD37 in cellular immunity appear contradictory. In vitro approaches indicate a negative regulatory role, whereas in vivo studies suggest that CD37 is necessary for optimal cellular responses. To resolve this discrepancy, we studied the adaptive cellular immune responses of CD37−/− mice to intradermal challenge with either tumors or model antigens and found that CD37 is essential for optimal cell‐mediated immunity. We provide evidence that an increased susceptibility to tumors observed in CD37−/− mice coincides with a striking failure to induce antigen‐specific IFN‐γ‐secreting T cells. We also show that CD37 ablation impairs several aspects of DC function including: in vivo migration from skin to draining lymph nodes; chemo‐tactic migration; integrin‐mediated adhesion under flow; the ability to spread and form actin protrusions and in vivo priming of adoptively transferred naïve T cells. In addition, multiphoton microscopy‐based assessment of dermal DC migration demonstrated a reduced rate of migration and increased randomness of DC migration in CD37−/− mice. Together, these studies are consistent with a model in which the cellular defect that underlies poor cellular immune induction in CD37−/− mice is impaired DC migration.